Job Creation and the Intra-distribution Dynamics of the Firm Size Distribution - Peter Huber; Harald Oberhofer; Michael Pfaffermayr (Austrian Institute of Economic Research (WIFO), 2011)
Based on a structural model for initial firm size, survival and firm growth we estimate firm-specific transition probabilities between size classes of the firm size distribution. This allows an assessment of the impact of different (counterfactual) economic policy measures on intra-distribution dynamics of the firm size distribution. We find that policies increasing the life span of firms reduce the exit hazard of young firms, but also reduce the probability to be a Gazelle. An increase in the industry-wide entry rate increases the exit hazards of incumbent firms and has no strong impact on the likelihood of firms to become Gazelles. Increasing market growth, by contrast, decreases the exit hazards for incumbent firms and slightly increases the likelihood of firms to be Gazelles. Finally, an increase in the birth size of firms increases the probability of young firms to be Gazelles with strongest effects for the smallest firms.
Keywords: 330; Firm growth; survival; entry size; Gazelles; economic policy; Unternehmenswachstum; Betriebsgröße; Markteintritt; Wirtschaftspolitik; Wirtschaftliche Anpassung; Industrie; Österreich